Filantropi Islam di Minangkabau: Membentuk Solidaritas Sosial Melalui Adat dan Agama - Deni Putra, Muhammad; Fadilla, Siti; Budia Warman, Arifki; Aliman Shahmi, Mohammad; Mansur, Muhammad (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This research focuses on Islamic philanthropy in Minangkabau and its contribution to building social solidarity through the integration of local customs and religion. The method used is a literature review, collecting data from relevant articles, books, and case studies. The purpose of this study is to explore how Minangkabau traditional values, such as